Lateralization Technique and Inferior Alveolar Nerve Transposition. (28th June 2016) - Pimentel, Angélica Castro; Sanches, Marco Antonio; Ramalho, Gabriel Cardoso; Roman-Torres, Caio Vinicius; Manzi, Marcello Roberto; Sendyk, Wilson Roberto
Abstract : Bone resorption of the posterior mandible can result in diminished bone edge and, therefore, the installation of implants in these regions becomes a challenge, especially in the presence of the mandibular canal and its contents, the inferior alveolar nerve. Several treatment alternatives are suggested: the use of short implants, guided bone regeneration, appositional bone grafting, distraction osteogenesis, inclined implants tangential to the mandibular canal, and the lateralization of the inferior alveolar nerve. The aim was to elucidate the success rate of implants in the lateralization technique and in inferior alveolar nerve transposition and to determine the most effective sensory test. We conclude that the success rate is linked to the possibility of installing implants with long bicortical anchor which favors primary stability and biomechanics.